Pendampingan Penyusunan Laporan Keuangan Fiskal SMKS Muhammadiyah Jatiroto Kab. Lumajang - Probowulan, Diyah; Feti Fatimah; Achmad Syahfrudin (Jurnal Pengabdian Masyarakat dan Lingkungan (JPML), 2025)
Community service activities at SMKS Muhammadiyah Jatiroto Lumajang aim to improve the understanding and skills of school managers related to tax obligations and financial management. With the increasing number of Muhammadiyah schools and the challenges faced in school tax management, this program is carried out through financial literacy training, tax calculation simulations, and assistance in the preparation of tax reports. During the period of January 6 to 8, 2025, the training was successfully attended by school managers, who showed a 75% increase in understanding after the training. The simulation of tax calculation and assistance in the preparation of tax reports also showed positive results, with 95% of participants able to complete their tasks well. This activity not only improves tax literacy, but also contributes to transparency and accountability in school financial management. The next stage plan includes evaluation, follow-up training, the formation of a tax management team, and socialization to stakeholders. Thus, this activity is expected to have a long-term impact on financial and educational management at SMKS Muhammadiyah Jatiroto and other schools around it.